2021
DOI: 10.1093/cvr/cvab108
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to mechanism-based atrial fibrillation ablation

Abstract: Modern cardiac electrophysiology has reported significant advances in the understanding of mechanisms underlying complex wave propagation patterns during atrial fibrillation (AF), although disagreements remain. One school of thought adheres to the long-held postulate that AF is the result of randomly propagating wavelets that wonder throughout the atria. Another school supports the notion that AF is deterministic in that it depends on a small number of high-frequency rotors generating three-dimensional scroll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…Despite improvements in ablation technology, imaging modalities, and ablation techniques, the recurrence of atrial arrhythmias after AF ablation still remains frequent [1,4]. Advances in mapping technologies have allowed for more detailed approaches, including panoramic and body-surface mapping for potential individual focal AF driver or rotational activity [5][6][7][8]. The elimination of these phenomena has also been linked to higher ablation success [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in ablation technology, imaging modalities, and ablation techniques, the recurrence of atrial arrhythmias after AF ablation still remains frequent [1,4]. Advances in mapping technologies have allowed for more detailed approaches, including panoramic and body-surface mapping for potential individual focal AF driver or rotational activity [5][6][7][8]. The elimination of these phenomena has also been linked to higher ablation success [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this therapeutic approach has not been reported. AF-driving excitations are complex, and therefore it’s important to establish a hierarchical criterion based on activation frequency so as to discern which alleged drivers are relevant for AF maintenance [ 6 ]. EXT seems to have the advantage of quantifying the burden of the single/multiple reentrant excitations in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Optical mapping experiments have demonstrated that single rotor and/or multiple wavelet excitations play a role in AF maintenance [ 4 , 5 ]; their elimination and/or modification are proposed as an effective ablation strategy for PeAF [ 6 ]. A previous non-invasive mapping study reported that PeAF was maintained predominantly by drivers clustered in a few regions.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these regions are empirically targeted for ablation without underlying mechanistic insights. The lack of target specifity can result in an extensive area of ablation [204]. The widely accepted mechanism underlying AF is that it is maintained by high-frequency drivers establishing a spatial hierarchy gradient of progressively slowing activation rates as the wavefronts propagate centrifugally from the source.…”
Section: Drug and Ablation Development Of Atrial Fibrillationmentioning
confidence: 99%